Electrocatalytic Hydrogenation of 5-Hydroxymethylfurfural in the Absence and Presence of Glucose - Kwon, Youngkook; de Jong, Ed; Raoufmoghaddam, Saeed; Koper, Marc T. M. (ChemSusChem, 2013)
Electrocatalytic hydrogenation of 5‐hydroxymethylfurfural (HMF) to 2,5‐dihydroxymethylfuran (DHMF) or other species, such as 2,5‐dimethylfuran, on solid metal electrodes in neutral media is addressed, both in the absence and in the presence of glucose. The reaction is studied by combining voltammetry with on‐line product analysis by using HPLC, which provides both qualitative and quantitative information about the reaction products as a function of electrode potential. Three groups of catalysts show different selectivity towards: (1) DHMF (Fe, Ni, Ag, Zn, Cd, and In), (2) DHMF and other products (Pd, Al, Bi, and Pb), depending on the applied potential, and (3) other products (Co, Au, Cu, Sn, and Sb) through HMF hydrogenolysis. The rate of electrocatalytic HMF hydrogenation is not strongly catalyst‐dependent because all catalysts show similar onset potentials (−0.5±0.2 V) in the presence of HMF. However, the intrinsic properties of the catalysts determine the reaction pathway towards DHMF or other products. Ag showed the highest activity towards DHMF formation (up to 13.1 mM cm−2 with high selectivity> 85 %). HMF hydrogenation is faster than glucose hydrogenation on all metals. For transition metals, the presence of glucose enhances the formation of DHMF and suppresses the hydrogenolysis of HMF. On poor metals such as Zn, Cd, and In, glucose enhances DHMF formation; however, its contribution in the presence of Bi, Pb, Sn, and Sb is limited. Remarkably, in the presence of HMF, glucose hydrogenation itself is largely suppressed or even absent. The first electron‐transfer step during HMF reduction is not metal‐dependent, suggesting a non‐catalytic reaction with proton transfer directly from water in the electrolyte. A clean sweep: The hydrogenation of HMF in neutral media has been studied on a wide range of solid metal electrodes both in the absence and in the presence of glucose. From HMF hydrogenation, three groups of catalysts show affinities towards (1) DHMF, (2) DHMF and other products, depending on applied potentials, and (3) other products. HMF hydrogenation is shown to be preferred to glucose hydrogenation on all metals.